Ответ:
1038
а) 5y(y² - 3)(y² + 3) = 5y(y⁴ - 9) = 5y⁵ - 45y
б) -8x(4x - x³)(4x + x³) = -8x(16x² - x⁶) = -128x² + 8x⁷ = 8x⁷ - 128x²
в) (a⁴ - 3)(a⁴ + 3)(a⁸ + 9) = (a⁸ - 9)(a⁸ + 9) = a¹⁶ - 81
г) (1 - b³)(1 + b³)(1 + b⁶) = (1 - b⁶)(1 + b⁶) = 1 - b¹²
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1038
а) 5y(y² - 3)(y² + 3) = 5y(y⁴ - 9) = 5y⁵ - 45y
б) -8x(4x - x³)(4x + x³) = -8x(16x² - x⁶) = -128x² + 8x⁷ = 8x⁷ - 128x²
в) (a⁴ - 3)(a⁴ + 3)(a⁸ + 9) = (a⁸ - 9)(a⁸ + 9) = a¹⁶ - 81
г) (1 - b³)(1 + b³)(1 + b⁶) = (1 - b⁶)(1 + b⁶) = 1 - b¹²